2018
DOI: 10.1007/s00259-018-4218-6
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of 18F-FDG PET/CT in diagnosing fracture-related infections

Abstract: Purpose 18 F-Fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET/CT) is frequently used to diagnose fracture-related infections (FRIs), but its diagnostic performance in this field is still unknown. The aims of this study were: (1) to assess the diagnostic performance of qualitative assessment of 18 F-FDG PET/CT scans in diagnosing FRI, (2) to establish the diagnostic performance of standardized uptake values (SUVs) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 21 publications
1
29
0
2
Order By: Relevance
“…Infection was correctly detected on visual analysis of FDG PET/CT scans in 23 patients, whereas two patients showed no increased FDG uptake and the scans were considered false-negative (diagnostic accuracy 81%). These results are consistent with those of the previous study (diagnostic accuracy 83%) by Lemans et al [13]. The authors concluded that FDG PET/CT is a promising tool for the specific evaluation of infected nonunion [16].…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Infection was correctly detected on visual analysis of FDG PET/CT scans in 23 patients, whereas two patients showed no increased FDG uptake and the scans were considered false-negative (diagnostic accuracy 81%). These results are consistent with those of the previous study (diagnostic accuracy 83%) by Lemans et al [13]. The authors concluded that FDG PET/CT is a promising tool for the specific evaluation of infected nonunion [16].…”
supporting
confidence: 92%
“…WBC scintigraphy and FDG PET provide higher accuracy for diagnosing FRI. Recently, two studies in a large homogeneous patient group with suspected FRI have been published [12,13]. In the first study [12], WBC scintigraphy was performed (using the correct dual time point imaging with decay correction, and the correct interpretation criteria according to EANM protocols [14,15]) in 192 consecutive patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent publication from our group has shown that the sensitivity and specificity of WBC scintigraphy to diagnose FRI in a large retrospectively analysed patient cohort is 0.86 and 0.98, respectively 31. In two other recent retrospective studies on the accuracy of FDG-PET/CT sensitivities and specificities between 0.65 and 0.89 and 0.77 and 0.80 are reported, respectively 32 33. Based on these results we expect a difference of at least 15% in sensitivity and specificity between the WBC scintigraphy and the FDG-PET/CT.…”
Section: Methods and Analysismentioning
confidence: 63%
“…Because physiologic images are relatively low in spatial resolution, 3 computed tomography (CT) has been combined with PET for both anatomical location and attenuation correction. PET/CT scanning is widely applied in the evaluating of tumors, cardiac disease, CNS disorders, and infection/inflammation [1,2].…”
Section: Introductionmentioning
confidence: 99%